Alkaline sulfite pretreatment for integrated first and second generation ethanol production: A techno-economic assessment of sugarcane hybrids. (December 2018) - Mendes, F.M.; Vasconcelos, M.H.; Dias, M.O.S.; Ferraz, A.; Milagres, A.M.F.; Santos, J.C.; Jesus, C.D.F.; Watanabe, M.D.B.; Junqueira, T.L.; Bonomi, A.
Abstract: Sugarcane hybrids have been developed through genetic engineering and plant breeding to produce lignocellulosic crops that are more susceptible for second generation biofuels production. Adequate evaluation of these plants requires process development combined with proper economic assessment. In this study, alkaline sulfite pretreatment of sugarcane biomass derived from four selected sugarcane hybrids was assessed for second generation ethanol production integrated with a first generation biorefinery. Process simulation and economic analysis were used to evaluate 32 biorefinery scenarios including different pretreatment conditions (high and low severity), enzymatic hydrolysis time (24 and 72 h) and pentoses destination (fermentation to ethanol or discard). Results indicated that high field productivity and low recalcitrance after pretreatment were critical characteristics for a selected sugarcane hybrid. High sodium sulfite loads were useful to increase ethanol production in the 1G2G biorefinery. However, sodium sulfite cost was relevant in the 1G2G ethanol cost. Sensitivity analysis applied to the best biorefinery scenarios indicated that maximum sodium sulfite prices to reach minimum acceptable rate of return (12%) were US 0.66/kg and US 0.47/kg for severe and mild pretreatments, respectively. Highlights: Techno-economic analysis presented the main bottlenecks of 1G2G ethanol production using alkaline sulfite pretreatment. Sodium sulfite used in the pretreatment step represented a significant fraction of the final 1G2G cost. Sensitivity analysis helped to evaluate the effect of sodium sulfite costs on the biorefinery IRR.